The Effectiveness Of Word Card As Media To Improve Students’ English Vocabulary - Fazriani, Ndita; Setianingsih, Tri; Firman, Edi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This research was aimed at finding out the effectiveness of word card to improve students’ english vocabulary. The subject of this study was 27 students at first grade of SMKN 1 Batulayar. In which consist of 16 males and 11 females. It was classroom action research, each cycle consist of four steps: planning, acting, observing and reflecting. The researcher used observation sheet to find out the activity during learning process and questionnaire to find out students improve in learning vocabulary. From this research, the students could improve their vocabulary by using word card. It proved in the first cycle, the students mean score was 72.7 there were 18 students passing KKM and the percentage was 66.6%. And it more improved in the second cycle, the students mean score 87.96 , there was all of students passing KKM and the percentage was 100%. Therefore, students become more enthusiastic and they were more active in learning English vocabulary. From those result the writer concludes that word card method is able to improve students’ English vocabulary of SMKN 1 Batulayar at first grade is successful.